Skull X-Rays for Head Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The effect of abolishing skull X-rays on the rate of admission, use of computer tomography (CT), radiation dose per head injury, and detection of intracranial injuries was determined in patients, aged 1 to 14 years, presenting to the ED at Royal Hospital for Sick Children, Edinburgh, UK.